The Effectiveness of Preschool Education on Social Adjustment of Elementary Students - Tahan, Mohammad; Kalantari, Masume (Indigenous, 2018)
Considering the physical, psychological and social preparation of the child in pre-primary school for advancement in various aspects of development and the certificate of various researches, the positive effect of this course's education on the social adjustment of primary school children requires more attention to pre-school education. The elementary school is useful and necessary in terms of quantitative and qualitative and conducting appropriate studies to evaluate the effects and improve the content and conduct of the training. The purpose of this study was to investigate the effectiveness of preschool education on social adjustment of primary school students.The method of this research is post-event (causal-comparative), in which a 320-person elementary school students (160 of whom had pre-primary education and 160 without pre-school education) had adaptive behavior questionnaires. Randomized sampling was performed and the results were analyzed. . Findings of this study showed that there is  no significant effect on pre-school education on social adjustment of elementary students. The results of this study confirm the view that children can not be sent to preschool centers in the hope that they will only have the effect of preschool experience on the development of their social adjustment, but also the quality of the programs of these centers, the personality and the way of communication. The teacher is the center of space and the amount of pre-school experience that matters in this area.Keywords: preschool education, social adjustment.